An experiment investigating the spill-over effects of voicing outrage - Anastasios Koukoumelis; M. Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
We report on an experiment designed to explore whether and how anger affects future levels of cooperation. Participants play three consecutive one-shot games. In between two identical two-person public goods games there is a mini dictator game that, depending on the treatment, either gives or does not give the recipient the opportunity to scold the dictator via a text message. We find that the recipients that receive an unfair offer contribute significantly less in the second public goods game. Yet, such contribution cuts are less frequent and notably smaller when messaging is allowed for. We conclude that although anger has a lasting negative effect on cooperation, giving voice to it helps to curtail selfishness.
Keywords: C72; C91; C92; D63; 330; dictator minigame; public goods game; emotions; cooperation; Nichtkooperatives Spiel; Emotion; Kooperation; Test